The Analysis of Allusion in Selective Songs of Matty Healy: in Pragmatic Context - Irfandy Triyono; Bahar Bahar; Basri Basri (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study is a qualitative research that aims to; (1) Find what types of allusions are contained in Matty Healy's songs; (2) How do these allusions function pragmatically to convey deeper layers of meaning in Matty Healy's lyrics. The data used in the study came from several collections of songs from the songs of the band The1975 written by Matty Healy and more specifically in the album entitled “The1975” from The1975. The data is in the form of words phrases or clauses that contain other meanings, or allusions pragmatically. The instrument of this research contains textual analysis, pragmatic theory as an analysis tool, reference and cross-referencing. The data analysis technique uses several methods, namely; (1) Identifying allusios, namely recognizing references in lyrics; (2) Contextual analysis, namely examining how meaning is shaped by the audience's backgroud knowledge; (3) Interpreting Meaning, namely exploring implied messages within the lyrics; (4) Cross-referencing, which is comparing Matty Healy's interviews, cultural context, and music reviews. As for the sample findings in this study, one of them is that it was found that Matty Healy wrote a song from the band The1975 on the album The1975 quite a lot of allusions.